2007
DOI: 10.1159/000098577
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Seborrheic Dermatitis Using Pramiconazole as a Potent Oral Anti-<i>Malassezia</i> Agent

Abstract: Background: Seborrheic dermatitis is considered to be a Malassezia-driven disease. Little objective information is available so far from biometrological quantitative assessments of this skin condition. Pramiconazole is a novel triazole with potent in vitro antifungal activity, especially against Malassezia spp. Objective: To study the sequential effects of pramiconazole on Malassezia, inflammation and epidermal changes. Method:This study was performed in 2 groups of subjects suffering from seborrheic dermatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
1
20
0
Order By: Relevance
“…An empirical piece of support for their pathogenicity is that known therapeutic materials are chemically diverse but have in common the property of potent anti-fungal activity (10). Also, it is generally accepted that effective therapies reduce the Malassezia load from the pretreatment level and that re-colonization of Malassezia post-treatment results in reoccurrence of the condition (11)(12)(13)(14)(15). A potential etiopathological mechanism (16) involves the lipolytic release of the fatty acid moieties from the parent sebaceous triglycérides by Upase activity originating from secreted Malassezia Upases (17); free fatty acids, especially unsaturated ones, can induce the inflammation and hyperproliferation (16) known to be components of D/SD leading to the commonly observed signs and symptoms associated with the conditions.…”
Section: Signs and Symptoms Of Dandruff And Seborrheic Dermatitismentioning
confidence: 99%
“…An empirical piece of support for their pathogenicity is that known therapeutic materials are chemically diverse but have in common the property of potent anti-fungal activity (10). Also, it is generally accepted that effective therapies reduce the Malassezia load from the pretreatment level and that re-colonization of Malassezia post-treatment results in reoccurrence of the condition (11)(12)(13)(14)(15). A potential etiopathological mechanism (16) involves the lipolytic release of the fatty acid moieties from the parent sebaceous triglycérides by Upase activity originating from secreted Malassezia Upases (17); free fatty acids, especially unsaturated ones, can induce the inflammation and hyperproliferation (16) known to be components of D/SD leading to the commonly observed signs and symptoms associated with the conditions.…”
Section: Signs and Symptoms Of Dandruff And Seborrheic Dermatitismentioning
confidence: 99%
“…Both pulse and continuous regimens for terbinafine were associated with clinical improvement [11][12][13]. The newer triazole pramiconazole has the lowest number of publications and it is still in development [14], but itraconazole is the most frequently reported oral treatment for SD [5]. The most commonly reported dosing regimen for itraconazole is a pulse regimen generally associated with an excellent therapeutic and safety profile in the treatment of moderate to severe SD [6,15,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…[25] While hepatotoxicity limits the use of ketoconazole, preliminary studies have indicated that both itraconazole and terbinafine are associated with fewer potential adverse effects. [5] In a recent pilot study, Pie´rard et al [14] found that a single 200-mg oral dose of pramiconazole decreased both the clinical symptoms of SD and the density of Malassezia colonies in lesional skin of ten patients with SD, while the control group (n = 17) experienced no change in their disease state. Conversely, oral fluconazole was recently found to have a marginal, but not statistically significant, effect in a placebo-controlled study of 50 patients with SD.…”
Section: Antifungal Treatmentsmentioning
confidence: 98%
“…The theory of the role of Malassezia in the pathogenesis of SD is strongly supported by the efficacy of antifungals in the treatment of the condition, the reduction in the number of Malassezia organisms after treatment, and studies showing that recolonization of Malassezia results in disease recurrence. [13] In a controlled study of 27 patients with SD, Pie´rard et al [14] found that treatment with pramiconazole first caused a decrease in the number of Malassezia colonies, which was followed by an improvement in the clinical signs of the disease.…”
Section: Malassezia In Seborrheic Dermatitis (Sd)mentioning
confidence: 99%